Impact assessment of fly ash on ground water quality: An experimental study using batch leaching tests. Issue 7 (July 2018) - Dandautiya, Rahul; Singh, Ajit Pratap; Kundu, Sanghamitra
The fly ash, generated at the coal-based thermal power plant, is always a cause of concern to environmentalists owing to its adverse impact on air, water and land. There exists a high environmental risk when it is disposed to the environment. Thus, two different type of fly ash samples (FA-1 and FA-2) have been considered in this study to examine the leaching potential of the elements magnesium, aluminium, silicon, calcium, titanium, vanadium, chromium, manganese, iron, nickel, cobalt, copper, zinc, arsenic, selenium, strontium, cadmium, barium and lead for different types of leachant. Toxicity characteristics leaching procedure and ASTM tests have been performed in the laboratory to simulate different natural leaching scenarios. Characterisation of samples have been done through X-ray diffraction and field emission gun scanning electron microscope. The effect of different liquid to solid ratios (i.e. 5, 10, 20 and 50) on the mobilisation of elements has been analysed. The results indicated that the maximum leaching of all elements occurred at a liquid to solid ratio of 5 except for arsenic, barium and silicon. The groundwater analysis has also been done to understand the actual effects of leachate. The elements presenting the highest leachability in the two fly ash samples under all tested conditions were magnesium, aluminium, silicon and calcium. It has been observed that calcium exhibits greater leaching effects than all other constituents. The study presented here has been found very useful for assessing contamination levels in groundwater owing to leaching effects of fly ash under different scenarios, which can be helpful to prevent spreading of the contaminants by efficient management of fly ash.